2020
DOI: 10.1038/s41598-020-58642-y
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α increases breast cancer stem-like cells through up-regulating TAZ expression via the non-canonical NF-κB pathway

Abstract: Breast cancer patients often suffer from disease relapse and metastasis due to the presence of breast cancer stem-like cells (BCSCs). Numerous studies have reported that high levels of inflammatory factors, including tumor necrosis factor alpha (TNF-α), promote BCSCs. However, the mechanism by which tnf-α promotes BCSCs is unclear. In this study, we demonstrate that TNF-α up-regulates TAZ, a transcriptional co-activator promoting BcSc self-renewal capacity in human breast cancer cell lines. Depletion of TAZ ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 51 publications
5
42
0
1
Order By: Relevance
“…Gao et al., also recently demonstrated that TNF-α mediates breast cancer cell migration through YAP signal activation, indicating the involvement of both canonical and non-canonical NF-κB signaling in this process ( 36 ). Moreover, TNF-α was reported to increase the proportion of breast cancer stem-like cells through NF-κB/HIF1α/Slug, indicative of primary breast tumors with self-renewal capacities that are resistant to cell death ( 37 ). TNF-α is also characterized by an imbalance between survival and apoptosis signals in many pathological situations, including cancer ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gao et al., also recently demonstrated that TNF-α mediates breast cancer cell migration through YAP signal activation, indicating the involvement of both canonical and non-canonical NF-κB signaling in this process ( 36 ). Moreover, TNF-α was reported to increase the proportion of breast cancer stem-like cells through NF-κB/HIF1α/Slug, indicative of primary breast tumors with self-renewal capacities that are resistant to cell death ( 37 ). TNF-α is also characterized by an imbalance between survival and apoptosis signals in many pathological situations, including cancer ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…TNFα enhances the CSC phenotype in numerous cell types and is associated with upregulation of stem cell related genes, chemo resistance and tumorigenesis [114][115][116]. Furthermore, TNFα upregulates TAZ (a Hippo pathway effector) and Slug (an EMT mediator), which increase breast CSCs through both canonical and non-canonical NF-κB signaling [117,118]. Analysis of TNBC patient datasets reveals high tumor expression of the epigenetic reader methyl-CpG-binding domain protein 2 (MBD2), specifically the alternative splicing variant 2 (MBD2_v2) expression and high relapse rate and high BMI [119].…”
Section: Immune Cells and Inflammatory Factorsmentioning
confidence: 99%
“…73 In addition, for the noncanonical NF-κB pathway it seems that TNF-α induces the expression of transcription adaptor putative zinc finger (TAZ), a transcriptional co-activator, and increases CSCs in both ER+ and TNBC cell lines. 74 TAZ do not bind to DNA directly, but can be recruited to specific target promoter sequences through binding to the TEAD transcription co-factor, and regulate the expression of genes that are essential for proliferation, apoptosis, and EMT. 75,76 NF-κB also contributes to the invasive and metastatic capabilities of CSCs, which can occur through modulation of the extracellular environment or through EMT.…”
Section: Wnt/β-catenin Signaling In Cscsmentioning
confidence: 99%